TINDAKAN HUKUM PEMERINTAH KOTA DENPASAR DALAM MELINDUNGI KEBERADAAN AIR TANAH DI KOTA DENPASAR - Budiadnyana Giri, Ketut Eddy; Arya Utama, I Made; Dahana, Cokorda Dalem (Kertha Desa; Vol. 01, No. 01, Maret 2013)
The legal action of Denpasar city government's to protect ground water presencein the Denpasar city. To preserve the environment, the government is taking legalaction to deliver the policy to the public in order to protect the existence ofgroundwater. Based on that there is a problem such as, firstly, how resources Denpasargovernment authority through the instrument permits the use of groundwater inprotecting groundwater in Denpasar. Second, if the soil permits water use can provideprotection against the presence of ground water in the city of Denpasar. Within thispaper, the method used is a normative legal research using regulatory approach. Theconclusions obtained are the source of government authority is in the Denpasar MayorRegulation No. 22 Year 2011 on setting Licensing, Allocation, Use, and GroundwaterExploitation, which has the function to limit and cope with the occurrence of a fraud aswell as the excessive exploitation of ground water. Prevailing source of authority overgroundwater use permits instrument and function of soil water use permit in order toprotect the existence of groundwater. Government observation and monitoring ofground water used by the community to the issuance of a license is an act ofgovernment.
Keywords: Denpasar, legal action, license, groundwater